Software protection system : binary control flow obfuscation for portable executables - Chew, Ron Jun Hong. (2012)
With the advancement of reverse engineering technology, the rise in software piracy and program hacking is becoming a worrying factor for software developers. Software developers are always on the lookout for cost-effective measures to protect their software.